Efeito da salinidade, densidade de estocagem e da infecção hipodermal e necrose hematopoiética (IHHN) na imunidade do camarão Litopenaeus vannamei cultivados em fazendas do Rio Grande do Norte - Reis, Lígia Garcia (2008)
The main problem faced by the shrimp industry are the infectious diseases. The hypodermal and hematopoietic necrosis infection (IHHN) is one of the major cause of disease in the cultured shrimp, Litopenaeus vannamei. Environmental changes involving water quality, oxygen concentration, salinity, temperature, stocking density, presence of pathogens, among others, triggering a stressing condition for the cultured shrimp, weakening them and allowing the outbreak of diseases. The stress on the animal leads to a change in the molecules immune response components, which can be used as indicators of shrimp health. Thus, the objective of the present study was to evaluate the effect of salinity, stocking density and IHHNV infection on the L. vannamei shrimp. The immune parameters used to check the shrimp health were the total hemocytes counts (THC), the agglutinating activity (AA) and the clotting time (CT) of the serum of shrimp. These parameters were analyzed in healthy and IHHNV-infected shrimp, grown in low (0-0.5 ), medium (19-24 ) and high (> 38 ) salinity, and extensive (7-12 cam.m-2), semi-intensive (15-25 cam.m-2) and intensive (33-45 cam.m -2) stocking density. The IHHNV infection rate was significantly higher in low salinity (P<0.005) and intensive density (P<0.005), both stressful conditions for L. vannamei. Low salinity significantly increased THC (P<0.05) and decreased and CT (P<0.05) in healthy and infected shrimp, but AA (P<0.05) significantly decreased in healthy shrimp at medium salinity. Culture intensification did not affect the THC, AA and CT of healthy and infected shrimp (P>0.05). The IHHNV infection did not affect any immune parameters of shrimp cultured at different salinities and stocking densities. It is necessary to emphasize that this study was conducted in shrimp grown in ponds, where several environmental factors are acting simultaneously. Thus, further studies are needed about the influence of other environmental factors on the immune parameters of shrimp cultured in pond